Juvenile delinquency and crime prevention - Guevara, Ricardo M. (Quezon City : Wisemans Books Trading, Inc., 2008)
"This book with the hope that will provide the basic model to promote and strengthen the solidarity and development of the family by ensuring that proper care, supervision and protection be given to our Nations most precious resource the Filipino youth."
English text.